Safety of anastomotic techniques and consequences of anastomotic leakage in patients with colorectal cancer: a single surgeon experience - Élthes, Etele (Med Pharm Rep, 2020)
INTRODUCTION: Colorectal cancer is a common type of malignant disease of the digestive tract. Anastomotic leakage (AL) still represents a serious complication in gastrointestinal surgery, associated with high morbidity and mortality. METHODS: We conducted a retrospective case-control study and analyzed a single surgeon’s data about 359 patients treated for colorectal cancer. Patients were divided as follows: Study Group (patients with AL - 37 patients) and Control Group (patients without AL - 322 patients). Surgical and anastomotic technique-related information was processed. RESULTS: Surgical procedures for right sided colon tumors resulted in a significantly lower rate of anastomotic leakage (P=0.0231). For left sided colectomies end to end handsewn double layer anastomosis presented decreased odds (OR=0.176). For sigmoid segmental resection end to end anastomotic techniques developed low rate of fistula formation (handsewn - OR=0.593, stapled - OR=0.685). Performing Dixon type surgical interventions, anastomotic techniques seemed without influence on anastomotic leak appearance (handsewn and stapled), although distal anastomoses were identified as significant risk factors for fistula formation (P=0.0017). In order to perform subtotal colectomy, side to side sutures (handsewn and stapled) seemed safe choices for anastomotic procedure (P=0.0073). Patient with anastomotic leakage suffered a significantly longer hospital stay (P=0.0079), presented higher rate of surgical reintervention (P=0.0001), increased mortality (P=0.0001) and elevated hospitalization costs (P=0.0079). CONCLUSION: Postoperative complications like anastomosis leakage significantly increase hospitalization period, necessity of surgical reintervention, mortality and financial costs. In order to avoid these unpleasant events, bowel anastomoses require standardization during surgery.